Recent Advances in Catalytic Systems for the Sustainable Synthesis of Ethyl Levulinate from Biomass - Mhd. Shaumi Al Anshar; Luqman Buchori; Didi Dwi Anggoro; Setia Budi Sasongko; Istadi (Advance Sustainable Science Engineering and Technology, 2025)
The esterification of levulinic acid to ethyl levulinate presents challenges in catalyst efficiency, reusability, and environmentally friendly process design, restricting commercial scalability.  This study examines recent studies on diverse catalysts, including Deep Eutectic Solvents (DES), homogeneous and heterogeneous systems, and their effects on yield.  DES is positioned as a more sustainable option, with yields as high as 99.8%, quicker reaction times, and a lower environmental effect.  While heterogeneous catalysts require harsher conditions and have reusability difficulties, DES provides a greener and more efficient alternative to produce ethyl levulinate.  Life cycle assessments (LCA) of DES procedures reveal reductions in energy usage and greenhouse gas emissions of up to 69.72%.  Future research should focus on improving DES recovery and scalability for industrial applications.  This effort supports the United Nations' Sustainable Development Goals (SDGs), namely SDG 7 (Affordable and Clean Energy), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action).